57. CLINICAL AND PARACLINICAL CHARACTERISTICS OF PATIENTS UNDERGOING LAPAROSCOPIC DISTAL GASTRECTOMY WITH D2 LYMPH NODE DISSECTION (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the clinical and paraclinical characteristics of patients with gastric cancer undergoing laparoscopic distal gastrectomy with D2 lymph node dissection at Nghe An General Friendship Hospital.Methods: A cross-sectional descriptive study was conducted on 90 patients diagnosed with gastric adenocarcinoma. Data were collected from medical records, preoperative laboratory and imaging results, and endoscopic findings.Results: Most patients presented with abdominal pain (97.8%), loss of appetite (84.4%), weight loss (77.8%), and belching or acid reflux (54.4%). The mean body mass index (BMI) was 20.57 ± 2.03 kg/m², with the majority falling within the normal range (81.1%). Regarding ASA score, most patients were classified as ASA 2 (46.7%) and ASA 3 (43.3%). Most lesions were ulcerative or ulcerative-vegetative in nature. Computed tomography revealed gastric wall thickening in 85.6% of cases and staging was primarily T3 (57.8%) and T4a (20%).Conclusion: Patients with advanced-stage gastric cancer exhibited prominent clinical and paraclinical features, which are crucial for guiding appropriate laparoscopic surgical interventions.
Keywords: gastric cancer; D2 dissection; clinical features; paraclinical features; endoscopy; computed tomography.